Increased prevalence of sex chromosome aneuploidies in specific language impairment and dyslexia. (9th October 2013) - Simpson, Nuala H; Addis, Laura; Brandler, William M; Slonims, Vicky; Clark, Ann; Watson, Jocelynne; Scerri, Thomas S; Hennessy, Elizabeth R; Bolton, Patrick F; Conti‐Ramsden, Gina; Fairfax, Benjamin P; Knight, Julian C; et al.
<x xml:space="preserve">Abstract</x> Aim Sex chromosome aneuploidies increase the risk of spoken or written language disorders but individuals with specific language impairment (SLI) or dyslexia do not routinely undergo cytogenetic analysis. We assess the frequency of sex chromosome aneuploidies in individuals with language impairment or dyslexia. Method Genome‐wide single nucleotide polymorphism genotyping was performed in three sample sets: a clinical cohort of individuals with speech and language deficits (87 probands: 61 males, 26 females; age range 4 to 23 years), a replication cohort of individuals with SLI, from both clinical and epidemiological samples (209 probands: 139 males, 70 females; age range 4 to 17 years), and a set of individuals with dyslexia (314 probands: 224 males, 90 females; age range 7 to 18 years). Results In the clinical language‐impaired cohort, three abnormal karyotypic results were identified in probands (proband yield 3.4%). In the SLI replication cohort, six abnormalities were identified providing a consistent proband yield (2.9%). In the sample of individuals with dyslexia, two sex chromosome aneuploidies were found giving a lower proband yield of 0.6%. In total, two XYY, four XXY (Klinefelter syndrome), three XXX, one XO (Turner syndrome), and one unresolved karyotype were identified. Interpretation The frequency of sex chromosome aneuploidies within each of the three cohorts was increased over the expected population frequency (approximately 0.25%) suggesting that genetic testing may prove worthwhile for individuals with language and literacy problems and normal non‐verbal IQ. Early detection of these aneuploidies can provide information and direct the appropriate management for individuals.